Improving Narrative Essay Writing through Elaboration of Deductive Paragraphs among Senior High School Students - Juliarsi Jufri; Toufik Boukel; Shakhzodabonu Yuldasheva (Journal of Language, Literature, and Educational Research, 2026)
Purpose of the study: This study aimed to identify the effective ways of using elaboration of deductive paragraphs in teaching writing, especially narrative essay writing, for twelfth-grade students of Senior High School Pesantren Modern Datok Sulaeman Putri Palopo. Methodology: This study used Classroom Action Research (CAR) with two cycles consisting of planning, acting, observation, and reflection. The participants were 18 students of class XII Natural science. The instruments included writing tests and observation sheets. Writing assessment covered content, organization, vocabulary, grammar, and mechanics using Heaton’s scoring rubric. Main Findings: The findings showed that students’ writing achievement improved significantly after applying elaboration of deductive paragraphs. In cycle I, the mean score was 63.61 and students were less active. In cycle II, the mean score increased to 78.27, with students becoming more active, reaching 72.2% active and 27.8% very active participation. Novelty/Originality of this study: This study offers a practical teaching strategy by applying elaboration of deductive paragraphs to improve students’ narrative writing skills. It emphasizes motivation, intensive guidance, peer-sharing, independent writing practice, and outdoor learning, which provide a more structured and engaging approach for developing writing competence in senior high school students.